Determination of concrete fracture parameters based on two-parameter and size effect models using split-tension cubes - Ince, Ragip (Pergamon-Elsevier Science Ltd, 2010)
The notched beam specimens have been commonly used in concrete fracture. In this study, the splitting-cube specimens, which have some advantages - compactness and lightness compared to the beams, were analyzed for the effective crack models: two-parameter model and size effect model. The linear elastic fracture mechanics formulas of the cube specimens namely the stress intensity factor, the crack mouth opening displacement, and the crack opening displacement profile were first determined for different load-distributed widths using the finite element method. Subsequently, four series of experimental studies on cubic, cylindrical, and beam specimens were performed. The statistical investigations indicated that the results of the split-cube tests look viable and very promising. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Splitting test; Fracture mechanics; Two-parameter model; Size effect model